A Critical Appraisal of the Most Recent Investigations on Ora-Pro-Nobis (Pereskia sp.): Economical, Botanical, Phytochemical, Nutritional, and Ethnopharmacological Aspects - Valéria Maria Costa Teixeira; Anielle de Oliveira; Emanueli Backes; Cristina Giatti Marques de Souza; Rafael Castoldi; Anacharis Babeto de Sá-Nakanishi; Lívia Bracht; Jurandir Fernando Comar; Rúbia Carvalho Gomes Corrêa; Fernanda Vitória Leimann; Adelar Bracht; Rosane Marina Peralta (Plants, 2023)
Pereskia aculeata Miller and Pereskia grandfolia Haw, known as ‘ora-pro-nobis’, are unconventional vegetables belonging to the Cactaceae family, native to the Americas and common in the northeast and southeast regions of Brazil. This review attempts to present a balanced account of both the methods used for obtaining extracts from the diverse parts of the plants and the results that were obtained in terms of their applicability to foods and other products with biological activities. Attention will also be devoted to the properties of their bioactives and their applications to real food products. Methods for obtaining extracts from the diverse parts of the plants will be analyzed, as well as the chemical nature of the bioactives that were hitherto identified. Next, the applicability of ora-pro-nobis in either its integral form or in the form of extracts or other products (mucilages) to the production of food and dietary supplements will be analyzed. The species have been extensively investigated during the last few decades. But, the determination of chemical structures is frequently incomplete and there is a need for new studies on texture determination and color evaluation. Further studies exploring the fruit and flowers of P. aculeata are also required.